(untitled) (Journal of the College of Basic Education, 2023)
Women enjoy a special place in Arab Muslim societies and historical writings, due to their enjoyment of a higher value in all societies in general. In every era of history, women were subject to a set of social customs and traditions, some of which were imposed on them, isolating them from society, and depriving them of some of their rights, such as education, for example. Some of them practiced it voluntarily and with her desire as part of her upbringing and the environment in which she was raised. And due to the lack of social studies, especially with regard to the conditions of women, so I liked to research the conditions of Iraqi Muslim women during the Ottoman era, specifically in Baghdad and Mosul, to see their conditions during that era.